Identity, Policy, and Prosperity Border Nationality of the Korean Diaspora and Regional Development in Northeast China - Park, Jeongwon Bourdais (China in Transformation, 2018)
This book offers a rare glimpse into China's Korean minority, which dominates the area bordering North Korea; even as Korea is riven into capitalist and communist societies, China's Koreans register this dilemma as one internal to the society they live in, in China's postindustrial Northeast. As this research makes clear, once driven by state investment in industry, the Northeast is now struggling to define its identity as a post-industrial region; the ethnic Koreans there even more so. This monograph provides a distinctive look at a group shaped by political turmoil, economic transformation, and cultural struggle; the study may offer an idea of what the future of the Korean peninsula itself might be, disentangling the puzzling contradictions and synergies between nationality, locality and development in China.